2016
DOI: 10.4236/jbm.2016.41013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormonal Contraceptives on the Total Antioxidants Status of Women from Isolo, Lagos State, Nigeria

Abstract: The use of hormonal contraceptives has been implicated in the depletion of serum antioxidants and resultant promotion of oxidative stress which is associated with various disorders including cardiovascular disease and cancer. This study investigated serum total antioxidant status (TAS) in women taking hormonal contraceptives and compared their results with non-contraceptive users (age-and sex-matched). Sixty women aged 30 -45 years, were enrolled for the study which included forty-five users of hormonal contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
5
2
0
Order By: Relevance
“…A statistically significant higher mean value of AST, ALT, and ALP among HC-users than the non-user control groups in the present study was in agreement with the findings from previous studies conducted in Egypt, Nigeria, and Iraq [ 37 , 39 – 42 ]. This observation could be attributed to the induction of liver enzymes associated with the administration of HCs; this may attributed to the effect of the Ethinylestradiol (EE) in HCs to increase the metabolic activities of the hepatocytes; larger doses of HCs cause adaptative changes by increasing the level of metabolic enzymes [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A statistically significant higher mean value of AST, ALT, and ALP among HC-users than the non-user control groups in the present study was in agreement with the findings from previous studies conducted in Egypt, Nigeria, and Iraq [ 37 , 39 – 42 ]. This observation could be attributed to the induction of liver enzymes associated with the administration of HCs; this may attributed to the effect of the Ethinylestradiol (EE) in HCs to increase the metabolic activities of the hepatocytes; larger doses of HCs cause adaptative changes by increasing the level of metabolic enzymes [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…For sample size calculation, Open epi software version 2.3 was used. The values of the outcome variable were taken from the previous study conducted in Nigeria [ 37 ]. The sample size was calculated for each independent variables, and the calculation that gave the maximum sample size was considered.…”
Section: Methodsmentioning
confidence: 99%
“…27 In this study, the total antioxidant level was significantly decreased among women using OCP. This result was in agreement with Palan et al (2010) and Adejumo et al 28 The behavior of molecules related to oxidative stress can differ according to types and doses of estrogen, progestogen, or the particular compounds of estrogen and progestogen. 29 Estrogens display an antioxidant activity by inhibiting the expression and function of the NADP+/NADPH oxidase, 30 by increasing the expression and level of activation of the endothelial isoform of the nitric oxide synthase (eNOS) 31 and by stimulating the expression and activity of the manganese SOD (MnSOD) and of the extracellular SOD (ecSOD).…”
Section: Discussionsupporting
confidence: 92%
“…33 Therefore it implies that the counteractive effect of progestin would result in a decrease in the serum total antioxidant status especially, in women taking either COCP. 28 In the current study, there is a significant decrease in serum NO in the OCP users as compared to the control group. A similar result was reported by Lobysheva et al 14 Hassan et al 15 observed that taking COCP resulted in a significant decrease in NO level.…”
Section: Discussionsupporting
confidence: 45%
“…Contraception is the deliberate avoidance of conception by using various devices, sexual practices, chemicals, drugs, or surgical techniques [ 1 ]. Hormonal contraceptives (HCs) are synthetic biological chemicals that have been used to prevent unwanted pregnancy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%